Chromosome substitution strain assessment of a Huntington’s disease modifier locus - Ramos, Eliana Marisa; Kovalenko, Marina; Guide, Jolene R.; St. Claire, Jason; Gillis, Tammy; Mysore, Jayalakshmi S.; Sequeiros, Jorge; Wheeler, Vanessa C.; Alonso, Isabel; MacDonald, Marcy E. (Mammalian genome, 2015)
Huntington’s disease (HD) is a dominant neurodegenerative disorder that is due to expansion of an unstable HTT CAG repeat for which genome-wide genetic scans are now revealing chromosome regions that contain disease-modifying genes. We have explored a novel human–mouse cross-species functional prioritisation approach, by evaluating the HD modifier 6q23–24 linkage interval. This unbiased strategy employs C57BL/6J (B6J) Hdh Q111 knock-in mice, replicates of the HD mutation, and the C57BL/6J-chr10 A/J /NaJ chromosome substitution strain (CSS10), in which only chromosome 10 (chr10), in synteny with the human 6q23–24 region, is derived from the A/J (AJ) strain. Crosses were performed to assess the possibility of dominantly acting chr10 AJ-B6J variants of strong effect that may modulate CAG-dependent Hdh Q111/+ phenotypes. Testing of F1 progeny confirmed that a single AJ chromosome had a significant effect on the rate of body weight gain and in Hdh Q111 mice the AJ chromosome was associated subtle alterations in somatic CAG instability in the liver and the formation of intra-nuclear inclusions, as well as DARPP-32 levels, in the striatum. These findings in relatively small cohorts are suggestive of dominant chr10 AJ-B6 variants that may modify effects of the CAG expansion, and encourage a larger study with CSS10 and sub-strains. This cross-species approach may therefore be suited to functional in vivo prioritisation of genomic regions harbouring genes that can modify the early effects of the HD mutation.